PERANCANGAN MODEL PENGUKURAN KINERJA BERBASIS BALANCED SCORECARD DAN TANGGUNG JAWAB SOSIAL LEMBAGA PERKREDITAN DESA DI KABUPATEN BULELENG - Ni Made Sri Ayuni (ARTHA SATYA DHARMA, 2017)
The purpose of this study to determine the design of the performancemeasurement model based on the concept of the Balanced Scorecard (BSC) andsocial responsibility (CSR) in the village credit institutions. Qualitative methodsare used to obtain in-depth information and intact from the standpoint relatedinformants. The study found that the financial perspective village creditinstitutions indicator is the ratio of capital adequacy, asset quality, reserves fordoubtful loans, the ratio of return on assets, cost effectiveness ratio to income, theratio of liquid assets and loans and pay attention to risk.Appropriate indicatorsto measure performance from the customer perspective is the level of interestrates, promotional activities and the types of products and variants. Appropriateindicator to measure the performance of a business process perspective that theaccount opening process, the length of service to the credit, the credit applicationprocess and duration of the loan disbursement.Appropriate indicator to measurethe performance of the learning and growth perspective is the level of education,teaching systems and productivity levels. Indicators of social perspective of CSRvillage credit institutions described by sections of the concept of Tri Hita Karana.